Cardiovascular risk of urate‐lowering drugs: A study using the National Database of Health Insurance Claims and Specific Health Checkups of Japan - Sono Sawada; Kazuhiro Kajiyama; Haruka Shida; Ryota Kimura; Yuki Nakazato; Toyotaka Iguchi; Yukio Oniyama; Chieko Ishiguro; Yoshiaki Uyama (Wiley, 2023)
Abstract In the present study, we aimed to investigate the association between urate‐lowering drugs and cardiovascular events, primarily focusing on the risk of febuxostat and topiroxostat when compared with allopurinol in Japan. We conducted an observational study with a cohort design using the National Database of Health Insurance Claims and Specific Health Checkups of Japan, including new urate‐lowering drugs users between August 1, 2010, and March 31, 2018. Exposure and control groups were defined based on the first prescription of urate‐lowering drugs as follows: febuxostat or topiroxostat for exposure groups, allopurinol for the control group, and benzbromarone for the secondary control group. The primary outcome was cardiovascular events, defined as a composite of acute coronary syndrome, cerebral infarction, and cerebral hemorrhage. Hazard ratios were estimated using a Cox proportional hazards model. The number of patients in each exposure and control group was 1,357,671 in the febuxostat group, 83,683 in the topiroxostat group, 1,273,211 in the allopurinol group, and 258,786 in the benzbromarone group. The adjusted hazard ratios for the cardiovascular risk were 0.97 (95% confidence interval [CI]: 0.95-0.98) for febuxostat and 0.84 (95% CI: 0.78-0.90) for topiroxostat groups. The benzbromarone group exhibited similar results. No increased cardiovascular risk was observed with febuxostat or topiroxostat when compared with allopurinol in patients with hyperuricemia in Japan. These results provide real‐world evidence regarding the cardiovascular risk associated with urate‐lowering drugs, indicating that no additional safety‐related regulatory actions are warranted in Japan.